2014
DOI: 10.1007/s10584-014-1102-7
|View full text |Cite
|
Sign up to set email alerts
|

Preface and introduction to EMF 27

Abstract: This Special issue of Climatic Change documents the main findings of Energy Modeling Forum Model Inter-comparison Project (MIP) number 27 (EMF 27) entitled "The EMF27 Study on Global Technology and Climate Policy Strategies". This study focused on the development and cross model comparison of results from a new generation of comprehensive international climate policy intervention scenarios focusing on technology strategies for achieving climate policy objectives. These scenarios enabled the community to exerci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
23
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(23 citation statements)
references
References 23 publications
(16 reference statements)
0
23
0
Order By: Relevance
“…In the past, such studies generally considered rather idealized conditions such as full participation of all regions and sectors in climate policy. However, more recently, models have also studied the achievability of the 2 C target under less idealized circumstances assuming limits in technology availability or reduced participation in international climate policy (Clarke et al, 2009;Kriegler et al, 2013b;Riahi et al, 2015;Weyant and Kriegler, 2014). Even in those cases, most models still identify scenarios that reduce emissions in line with the 2 C target.…”
Section: Introductionmentioning
confidence: 99%
“…In the past, such studies generally considered rather idealized conditions such as full participation of all regions and sectors in climate policy. However, more recently, models have also studied the achievability of the 2 C target under less idealized circumstances assuming limits in technology availability or reduced participation in international climate policy (Clarke et al, 2009;Kriegler et al, 2013b;Riahi et al, 2015;Weyant and Kriegler, 2014). Even in those cases, most models still identify scenarios that reduce emissions in line with the 2 C target.…”
Section: Introductionmentioning
confidence: 99%
“…Studies at the global level (such as in Krey et al, 2014;Weyant and Kriegler, 2014) and regional level (Calvin et al, 2012;Clarke et al, 2012, for Asia;Clarke et al, 2014aClarke et al, , 2014bFawcett et al, 2014, for the USA; Knopf et al, 2013, for Europe) come to the same conclusion in this respect. For large-scale low-CO 2 electricity generation, renewables like solar and wind energy dominate the present view of many analysts on future global energy systems.…”
Section: Discussion Conclusion and Policy And Strategy Implicationsmentioning
confidence: 82%
“…renewables versus nuclear energy in this respect, see Macknick (2011). Weyant and Kriegler, 2014). The reason that EPPA and Phoenix do not increase their electricity generation as much as the other models is again that these CGE models have substantially lower overall energy demand, induced by sizeable losses in GDP, which is matched by relatively high CO 2 prices (see Fig.…”
Section: Electricity Productionmentioning
confidence: 97%
See 1 more Smart Citation
“…Besides SSP-related studies, several articles have studied the impact of societal change on climate change mitigation by looking at, for example, technological change [7,8], lifestyle change [9][10][11][12][13], energy efficiency [14][15][16] and biomass [17][18][19]. The EMF27 study employed scenarios focusing on technology variations, including energy-intensity improvement, technology availability and constraints [20]. Several papers emerging from EMF27 found that the mitigation costs could be dramatically reduced by technological innovation [21][22][23].…”
Section: Introductionmentioning
confidence: 99%